Quality Risk Management in Infusation Product Distribution Using Failure Mode and Effect Analysis (FMEA) and Analytical Hierarchy Process (AHP) Methods - Elis Dwiana Ratnamurni; Eka Ludiya; Amanda Luthfiartie (International Journal of Science, Technology & Management, 2022)
This study aims to determine the causes of product leaks so as to minimize the risks of product quality degradation. The research method used is descriptive qualitative research method, data collection techniques used are observation, interviews and documentation. The collected data is then analyzed to obtain useful information to solve a problem in research. The process of testing the validity and reliability in this study uses a triangulation process. In this study, to measure Quality Risk Management, FMEA is used as a tool to measure or identify the source or cause of a quality problem. The next method to solve problems or risks in Quality Risk Management is AHP. The results of the study can be concluded that, Quality Risk Management in the distribution of Infusion products. The risk with the highest RPN value is the risk of damaged goods in the distribution flow of releasing goods from the warehouse to the expedition of PT. BSP which causes a leak in the softbag packaging. These risks are then analyzed to find the best alternative for handling them. Determine alternative handling of Quality Risk Management in the distribution of Infusion products at PT. BSP using the AHP method. Based on calculations using Expert Choice 11 software, the priority criteria are time and handling effectiveness which has the highest pairwise comparison value is the alternative of adding product handling information labels on cardboard packaging.